2021
DOI: 10.1097/pts.0000000000000861
|View full text |Cite
|
Sign up to set email alerts
|

Medication Errors in the Operating Room: An Analysis of Contributing Factors and Related Drugs in Case Reports from a Japanese Medication Error Database

Abstract: ObjectiveThe aim of this study was to prevent drug-related medication errors in the operating room by clarifying the association between the medication error category with related drugs and contributing factors.MethodsWe used data from the Japan Council for Quality Health Care’s open database on the web. We researched the medication error category, related drugs, and contributing factors. We classified each medication error category into case groups and other medication error categories into control groups. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…A cross-sectional study conducted in Japan to analyze the factors associated with MAEs found increased number of administrations and frequent doses to be significantly associated with increased risk of MAEs. 59…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study conducted in Japan to analyze the factors associated with MAEs found increased number of administrations and frequent doses to be significantly associated with increased risk of MAEs. 59…”
Section: Discussionmentioning
confidence: 99%
“…18 One of the most common perioperative medication errors is associated with contraindications for administration; inadequate documentation and lack of information sharing are two reasons why this type of error occurs. 19 Effective communication among interdisciplinary team members and across different phases of perioperative care can be a key strategy for preventing medication errors. 18 To enhance team communication, a perioperative staff member should record the patient's allergies in a location that all personnel can see during the procedure.…”
Section: Strategies To Considermentioning
confidence: 99%
“…To ensure safe administration of long‐acting extended‐release local anesthetics, all perioperative team members should be aware of the relevant information associated with the medication, including its side effects and contraindications 18 . One of the most common perioperative medication errors is associated with contraindications for administration; inadequate documentation and lack of information sharing are two reasons why this type of error occurs 19 . Effective communication among interdisciplinary team members and across different phases of perioperative care can be a key strategy for preventing medication errors 18 .…”
Section: Strategies To Considermentioning
confidence: 99%
“…A relationship between medication factors such as related medication has been reported [ 3 , 4 ]. In addition, the number of medications and administrations per day, Medication Regimen Complexity Index (MRCI), which indicates the complexity of prescribing in self-management were reported to be associated with adherence and medication error [ 5 9 ].…”
Section: Introductionmentioning
confidence: 99%